IMMUNOLOGICAL AND METABOLIC FACTORS INTERACTION IN THE DEVELOPMENT AND PROGRESSION OF MICROVASCULAR COMPLICATIONS IN LATENT AUTOIMMUNE DIABETES OF ADULTS (LADA) - T. V. Saprina; T. S. Prokhorenko; F. E. Lazarenko; I. N. Vorozhtsova; N. V. Ryazantseva (Бюллетень сибирской медицины, 2014)
Some researchers found that the development of microvascular complications (nephropathy, retinopathy) with latent autoimmune diabetes adults (LADA) occurs much earlier than in type 1 diabetes mellitus. The research devoted to the study of the spectrum and the time of development of microangiopathy in patients with latent autoimmune diabetes of adults, compared to patients with type 1 and 2 diabetes mellitus. Also studied immunological factors (cytokine secretion of mononuclear leukocytes) as one of the possible mechanisms of diabetic angiopathy progression. It has been shown that in LADA, as in patients with type 2 diabetes mellitus, the development of microvascular complications (nephropathy, retinopathy) occurs much earlier than in type 1 diabetes mellitus (after a 4-year course of the disease) due to a sharp decline in the serum concentration of C peptide. Thus in patients with LADA, having microvascular complications in the supernatants of cell cultures of mononuclear leukocytes determined a significant increase in the concentrations of cytokines IL-2, IL-4, TNFα.